Individual differences in the encoding of contextual details following acute stress: An explorative study. (15th December 2020) - Sep, Milou S. C.; Joëls, Marian; Geuze, Elbert
Abstract: Information processing under stressful circumstances depends on many experimental conditions, like the information valence or the point in time at which brain function is probed. This also holds true for memorizing contextual details (or 'memory contextualization'). Moreover, large interindividual differences appear to exist in (context‐dependent) memory formation after stress, but it is mostly unknown which individual characteristics are essential. Various characteristics were explored from a theory‐driven and data‐driven perspective, in 120 healthy men. In the theory‐driven model, we postulated that life adversity and trait anxiety shape the stress response, which impacts memory contextualization following acute stress. This was indeed largely supported by linear regression analyses, showing significant interactions depending on valence and time point after stress. Thus, during the acute phase of the stress response, reduced neutral memory contextualization was related to salivary cortisol level; moreover, certain individual characteristics correlated with memory contextualization of negatively valenced material: (a) life adversity, (b) α‐amylase reactivity in those with low life adversity and (c) cortisol reactivity in those with low trait anxiety. Better neutral memory contextualization during the recovery phase of the stress response was associated with (a) cortisol in individuals with low life adversity and (b) α‐amylase in individuals with high life adversity. The data‐driven Random Forest‐based variable selection also pointed to (early) life adversity—during the acute phase —and (moderate) α‐amylase reactivity—during the recovery phase —as individual characteristics related to better memory contextualization. Newly identified characteristics sparked novel hypotheses about non‐anxious personality traits, age, mood and states during retrieval of context‐related information. Abstract : Theory‐ and data‐driven perspectives were used to explore individual characteristics that contribute to memory contextualization of different valenced information during the acute and recovery phase of the stress response. Life adversity and trait anxiety modulate the stress‐response, thereby impacting memory contextualization following acute stress. Other findings sparked new hypothesis about non‐anxious personality traits, age, mood and states during retrieval.